Application of riparian buffer zone in agricultural non-point source pollution control—A review - Wu, Shaoteng; Bashir, Muhammad Amjad; Raza, Qurat-Ul-Ain; Rehim, Abdur; Geng, Yucong; Cao, Lei (Frontiers in Sustainable Food Systems, 2023)
Water is an important natural element of our environment, and its management and security are also serious concerns. Agricultural non-point source pollution (NPSP) is one of the major sources of contaminants causing water quality degradation. A riparian buffer zone is a vegetative cover adjacent to water channels that positively contributes to pollutant filtration and sediment trapping. It has the potential to filter nutrients, reduce nutrients and pesticide leakage, provide habitat and protection against floods, minimize erosion issues, improve biodiversity and ecological connectivity, and add aesthetics to the area. Moreover, it is inexpensive and requires little maintenance making buffer zone an attractive approach to NPSP control. In this review, we have enlightened the effects of the riparian buffer zone on water quality and agricultural NPSP and how its structures and mechanisms contribute to controlling water pollution effectively. We conclude that the riparian buffer zone is an effective technique for water safety, NPSP control, and creating a suitable environment for terrestrial and aquatic species. Moreover, it has the potential to reduce the water temperature due to the shading effect and sustain water habitat acting as a climate adaptation tools. Buffer zones should be adopted for agricultural non-point source pollution and achieve environmental sustainability. However, the long-term influence of the riparian buffer zone on trapping NPS pollutants, soil properties, and groundwater quality is s research gap.